UNGKAPAN BAHAGIA SISWA DALAM KEGIATAN PERAYAAN HARI KEMERDEKAAN 17 AGUSTUS DI SMAN 7 MAROS - Sukmawati; Amir, Johar; Hasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of students’ expressions of happiness during the celebration of Indonesia’s Independence Day on August 17 at SMAN 7 Maros and to explain the intentions underlying these expressions. This research employs a qualitative approach with a descriptive qualitative design. The primary data consist of students’ expressions of happiness, while the data sources are all students of SMAN 7 Maros who actively participated in the Independence Day celebrations, including competition participants, ceremony participants, performers in art performances, and other activities involving social interaction. The data emerged spontaneously during the course of the celebrations. The data were collected through observation, listening techniques, and documentation, and were analyzed using Searle’s theory of expressive speech acts combined with Goleman’s theory of emotional intelligence. The results show that all identified utterances belong to expressive speech acts that reflect the psychological states of the speakers. The forms of students’ expressions of happiness include encouragement, cheerfulness, joy, pride, admiration, satisfaction, congratulating, gratitude, and thankfulness. Expressions of admiration were the most dominant, while expressions of satisfaction, gratitude, and thankfulness were the least frequently found. In terms of intention, expressions of happiness function not only as expressions of positive emotions but also as a means, namely to provide support, convey appreciation, and strengthen togetherness and social relationships among students. These findings indicate that students’ emotional intelligence can be observed through language use in social interactions during the celebration. Thus, language plays a central role as a medium for expressing emotions and building solidarity in the context of Independence Day celebrations in the school environment